Profile of Childhood Glaucoma at a Tertiary Eye Care Centre in North East India - Charu Arora; Shahinur Tayab; Harsha Bhattacharjee; Techi D. Tara; Mohammed Sithiq; Manjisa Choudhary (TNOA Journal of Ophthalmic Science and Research)
Purpose: To report the prevalence of various forms of childhood glaucomas visiting our tertiary eye care centre during a year and to describe their clinical features and treatment methods. Methods: This 1-year-long prospective study included all the consecutive children till 16 years of age who presented to us with glaucoma for the first time between 1 March 2022 and 28 February 2023. We used the Childhood Glaucoma Network Classification System for the classification of glaucoma. Results: Of the 40 children (80 eyes), secondary childhood glaucoma (SCG) was diagnosed in 76.5% of eyes, while primary childhood glaucoma (PCG) was in 23.5% of eyes. Eleven patients (27.5% eyes) had bilateral involvement. Glaucoma due to acquired ocular conditions was the most common diagnosis (49% of eyes) in the SCG group, followed by glaucoma secondary to non-acquired ocular conditions (21.5%), glaucoma with non-acquired systemic disorder (1.96%), and glaucoma status post cataract surgery (3.92%). In the PCG group, infantile glaucoma was the most common (13.7%), followed by juvenile (5.9%) and late-onset/recognised PCG (3.92%). The mean intra-ocular pressure at presentation was 30.25 mmHg in the PCG group and 36.54 mmHg in the SCG group. The male-to-female ratio was 7:1 in both the PCG and SCG groups. Around 63% of eyes needed surgical intervention (filtration or other); however, only 13.7% underwent surgery. 69% of the eyes received medical treatment only; this group includes the PCG patients who left without undergoing surgery. Around 17.6% of the eyes needed anti-glaucoma medications after surgery. Both glaucoma filtration surgery and vitreo retinal surgery were the most common surgeries (12.5% each) performed overall. Conclusion: In our cohort, SCG was found to be the most prevalent sub-type of CG, with better treatment compliance and outcomes in contrast to PCG with poor treatment compliance and outcomes. Sensitisation of the masses to this blinding disease is crucial to bring about desired changes in the existing scenario.